A cross sectional, analytical study of personal hygiene related morbidities of children residing in welfare hostels, Tirupati town, Andhra Pradesh, India - Ravi Naik, Karamthoti; Srinivasan, K.; Raviprabhu, G.; Reddy, K. Ashok Kumar; Prameela, B. (International Journal Of Community Medicine And Public Health, 2020)
Background: The objective of the study was to find out the personal hygiene status among boys residing in social welfare hostels by class and age and type of hostel. Methods: Cross sectional study, analytical study, social welfare hostels in Tirupati town of Andhra Pradesh. Participants was 524 boys. Statistical analysis are percentages and Chi-square test. Results: The prevalence of scabies was found to be significantly higher in those children with poor personal hygiene (35.7%) compared to average level (18.8%) and good (14.4%) of personal hygiene. The prevalence of other specific morbid conditions was found to be similar in all the three levels of personal hygiene and the differences were not statistically significant. Conclusions: The prevalence of scabies was found to be significantly higher in those children with poor personal hygiene compared to average level and good of personal hygiene. In view of higher proportion of children with poor level of personal hygiene of children in scheduled tribe hostel, there is a need to sensitize and give health education on personal hygiene related diseases and take necessary preventive steps and supervision by hostel staff especially in scheduled tribe hostel. Hand washing with soap can protect about one out of every three young children.